Porous carbon-coated ZnO nanoparticles derived from low carbon content formic acid-based Zn(II) metal-organic frameworks towards long cycle lithium-ion anode material. (10th October 2016) - Gao, Song; Fan, Ruiqing; Li, Bingjiang; Qiang, Liangsheng; Yang, Yulin
Graphical abstract: The nanocomposites constructed from Zn-based MOFs exhibit low carbon content with super-high rate capability and long cycling life. Highlights: Novel ZnO@porous carbon matrix nanocomposites are constructed by pyrolysis of Zn-based MOFs. The nanocomposites constructed with Zn-based MOFs show low carbon content. The constructed nanocomposites exhibit high energy density, super-high rate capability and long cycling life. Abstract: Single-C formic acid-based metal-organic frameworks (MOFs) are used to construct novel ZnO@porous carbon matrix nanocomposites by controlled pyrolysis. In the constructed nanocomposites, the porous carbon matrices act as a confined support to prevent agglomeration of the ZnO nanoparticles and create a rapid electron conductive network. Meanwhile, the well-defined, continuous porous structured MOFs provide a large specific surface area, which increases the contact of electrolyte-electrode and improves the penetration of electrolyte. Especially, the reasonable choice of formic acid-based MOFs construct the low carbon content composite, which contribute to the high energy density and long cycle life. The constructed nanocomposites show stable, ultrahigh rate lithium ion storage properties of 650 mAh g −1 at charge/discharge rate of 1 C even after 200 cycles.